Community Health Workers: An Untapped Resource to Promote Genomic Literacy. (1st August 2016) - Allen, Caitlin G.; McBride, Colleen M.; Balcazar, Hector G.; Kaphingst, Kim A.
Abstract : Poor understanding of gene–environment contributors to health conditions can lead the public to misinterpretations that overemphasize genetics as determinants of health. The present commentary calls for engaging the national community health worker (CHW) workforce to use community elicitation methods such as mental models approaches as a means to enhance the public's literacy regarding genetic and environmental or genomic contributions to health. We discuss three needs related to genomic literacy and suggest how CHWs are uniquely positioned to address these needs among diverse target audiences. We conclude by offering directions for the future of CHWs working to build genomic literacy.